The Role of Leadership and Motivation in Improving Employee Performance - Nurodin, Idang; Alhidayatullah, Alhidayatullah; Sudarma, Ade (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2023)
Purpose – This research was conducted at the Office of Youth and Sports, Tourism and Creative Economy (Disporapar). The purpose of this study was to determine the influence of leadership dan motivation on the performance of employees of the Youth and Sports, Tourism and Creative Economy Services (Disporapar). Methodology/approach – The population in this study was 43 people from the Youth and Sports, Tourism, and Creative Economy Service (Disporapar). The method of determining samples in this study used saturated or census samples. The data used are primary data and secondary data. The data analysis method used is the multiple linear regression method. Findings – The findings demonstrated that motivation and leadership have a favorable impact on worker performance. Leadership and motivation had a 60.1% impact on staff performance, while other factors had a 39.9% impact. And the dominant variable that affects employee performance is the leadership variable, it can be concluded that the leadership in the Youth and Sports, Tourism, and Creative Economy Service (Disporapar) has been good in influencing employee performance. Novelty/value – This research discusses theories about human resources and contributes to expanding the literature on leadership, organizational culture, and employee performance from the organizational context.